Penurunan Residu Pestisida Pada Buah Dan Sayur Menggunakan Larutan Eco Enzyme Dan Sabun Produk Pabrik Z Tahun 2023 - Sri Ani; Agus Riyanto; Benedicta Tiara Nindiakristi (CV. Multi Kreasi Media, 2023)
Based on data from The Economics Intelligence Unit for 2021, Indonesia is the second largest producer of food waste in the world. Several innovations have sprung up to overcome this, one of which is Eco Enzyme, which is a multi-purpose liquid that can be used in everyday life such as mopping floors, cleaning dishes, washing fruits and vegetables, and others. Eco Enzyme is made from fruit peel waste, brown sugar and clean water. Based on the author's interest in using Eco Enzyme as a fruit and vegetable wash, research was carried out on the manufacture of Eco Enzyme and used as a fruit and vegetable wash and researched the reduction of pesticide residue levels in fruits and vegetables. This type of research is an experiment with a pretest and posttest group design. The population in this study were fruits and vegetables which were suspected of using pesticides from plantations in Kuningan Regency, West Java. Hence the research entitled